Vocational Campus Readiness In The Disruption Era: A Case Study In Aviation Polytechnic of Surabaya - Winiasri, Linda; Nurlaela, Luthfiyah; Sumbawati, Meini Sondang (Universitas Malikussaleh, 2020)
The era of disruption requires change and adaptation in all fields. The education sector is also expected to be able to adapt, especially for vocational education. How graduates from vocational education should be, and how the readiness of vocational campus in dealing with it. This research is a preliminary study using a literature review and observation approach on the Surabaya Aviation Polytechnic as one of the vocational colleges of the Ministry of Transportation. Campus readiness is measured by the competence and skills of cadets, as well as the education carried out there. Competence and preparedness of cadets are measured from critical thinking and problem solving skills, collaboration and leadership, dexterity and adaptability, initiative and entrepreneurial spirit, able to communicate effectively both orally and in writing, able to access and analyze information, and have curiosity and imagination. The next discussion is about learning, how education is carried out. Education is carried out based on four pillars of education, namely learning to know, lerning to do, learning to be and learning to live together. College readiness is also measurable and achievable, which is overseen by the Quality Assurance Unit and the Internal Inspection Unit who continue to work to ensure that the Quality Standards continue to run in accordance with established regulations. Suggestions offered for the Surabaya Aviation Polytechnic are to keep on updating the development of the aviation industry, continue to improve cooperation with stake holders, and continue to improve the quality of human resources educators and management.